(untitled) (Contemporary Mathematics, 2024)
In this paper, we explain the sufficient conditions on a novel constructed stochastic space by weighted generalized Gamma matrix and variable exponent sequence spaces of fuzzy functions, for the Kannan contraction operator to have a unique fixed point. Finally, we discuss the numerous applications of solutions to Fuzzy Volterra-Type Non-linear Dynamical Economic Models and illustrate them with some examples.